A novel multiplex detection array revealed systemic complement activation in oral squamous cell carcinoma - Gallenkamp, Juliane; Kirschfink, Michael (OncoTarget, 2018)
Oncotarget | https://doi.org/10.18632/oncotarget.22963 Juliane Gallenkamp, Gerrit Spanier, Elisabeth Wörle, Markus Englbrecht, Michael Kirschfink, Roman Greslechner, Regine Braun, Nicole Schäfer, Richard J....